Evaluation of the Maturity Level of the RS SIM System using the Cobit 5 Framework in the Evaluation Direct and Monitoring Domain - Rezeki, Yunika Tri; Oktadini, Nabila Rizky; Putra, Pacu; Sevtiyuni, Putri Eka; Meiriza, Allsela (Sistemasi: Jurnal Sistem Informasi, 2025)
The purpose of using the COBIT 5 framework in the Evaluate, Direct, and Monitor (EDM) domain in this study is to assess the maturity level of the Hospital Information Management System (HIMS) at the Primaya Hospital Laboratory. The evaluation process focuses on three main aspects: EDM01 (Governance Framework Setting and Maintenance), EDM02 (Ensuring Risk Optimization), and EDM05 (Ensuring Transparency). Data were collected by involving the hospital’s IT team through questionnaires and interviews. Based on the analysis, the current maturity level of the HIMS ranges from level 2 to level 4, with a target of achieving level 4 (Predictable Process). A GAP analysis was conducted to compare the current system condition (as-is) with the desired condition (to-be). This study provides improvement recommendations, including the optimization of system governance and the enhancement of IT performance transparency. These recommendations are expected to support increased efficiency, effectiveness, and the strategic value of the Hospital Information Management System (HIMS) at Primaya Hospital.